The Flag-Raising - Wiggin, Kate Douglas Smith, 1856-1923 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Flag-Raising" by Kate Douglas Smith Wiggin is a children's novel written in the early 20th century. The story revolves around a young girl named Rebecca Randall as she navigates life with her strict aunts in Riverboro, Maine, during a time when community and patriotism are significant. The narrative captures themes of childhood, education, and local customs, primarily focusing on the excitement and preparation surrounding a flag-raising ceremony, reflecting the innocence and aspirations of youth. In the book, Rebecca arrives at her aunts' home, where she is initially worried about fitting in due to her unconventional ways. As she tries to adapt to her new life, her spirit shines through her love for poetry and her imaginative nature. Set against the backdrop of the flag-raising event, Rebecca becomes an integral part of the preparations to create the community's flag, ultimately embodying the State of Maine during the ceremony. The story highlights her determination and creativity, especially in a tense moment when she must recover the stolen flag. The charming and humorous incidents throughout demonstrate Rebecca$1 (Bs resilience, her relationships with her family and peers, and the underlying message of unity, pride, and belonging to something greater than oneself. (This is an automatically generated summary.)s
A difference in hearts $1 (BRebecca's point of view $1 (BWisdom's ways $1 (BThe saving of the colors $1 (BThe state o' Maine girls
Release date is 2000-09-01
Produced by Susan L. Farley. HTML version by Al Haines.
Keywords: Short stories; United States -- Juvenile fiction